Additional data support the role of LINC00673 rs11655237 C>T in the development of neuroblastoma - Li, Yong (Aging (Albany NY), 2019)
Neuroblastoma is the most frequently diagnosed neural tumor of childhood. Abnormal function of the long intergenic non-coding RNA (lincRNA) LINC00673 has been implicated in various human malignancies. Genome-wide association studies revealed the LINC00673 rs11655237 C>T polymorphism to be associated with the risk of neuroblastoma, though the effect was not well defined, in part due to the small sample size in our earlier study. Herein, we verified the impact of LINC00673 rs11655237 C>T on the risk of neuroblastoma in 700 cases and 1516 controls from six centers in China. After pooling all enrolled patients, we observed a significant association between LINC00673 rs11655237 C>T and risk of neuroblastoma (TT vs. CC: adjusted odds ratio [OR]=1.58, 95% confidence interval [CI]=1.06–2.35, P=0.024; additive model: adjusted OR=1.20, 95% CI=1.03–1.39, P=0.020; recessive model: adjusted OR=1.50, 95% CI=1.02–2.22, P=0.040). Stratification analysis revealed a significant relationship between rs11655237 CT/TT and neuroblastoma risk in subgroups of males, patients whose tumor originated in the adrenal gland, and patients with clinical stage IV disease. These findings add new evidence of the importance of LINC00673 rs11655237 C>T to the risk of developing neuroblastoma.